THE IMPORTANCE OF STUDYING THE ISSUES OF CREATING EDUCATIONAL VOCABULARY OF PRIMARY GRADE MOTHER TONGUE TEXTBOOKS (TAMADDUN NURI JURNALI, 2024)
In this article, the issues of creating educational dictionaries are studied, the important aspects of creating educational dictionaries of elementary school mother tongue textbooks are scientifically based. The goals and tasks of creating the textbooks of primary grade native language textbooks are disclosed.